Analisis SWOT terhadap Produk Unggulan Pertanian di Humbang Hasundutan: Studi Pengolahan Produk Bernilai Tambah - Simamora, Vailimlim; Simbolon, Irma Chintia; Margaret, Natasia Theofani; Situmorang, Elsaday Ria Veronika (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research aims to explore economic growth in this region using the Location Quotient (LQ) approach and SWOT Analysis on leading commodities in Humbang Hasundutan Regency, especially in the agricultural sector. This regency has significant potential in developing corn as one of the leading products with added value and contributing to the Regional Gross Domestic Product (PDRB). The methods applied include quantitative analysis based on secondary data from BPS (2021–2023) and SWOT analysis to identify strengths, weaknesses, opportunities, and threats in the development of corn-based products. The results of the LQ calculation show that corn has an LQ value above 1 (average 1.57), indicating competitive advantage and export potential between regions. The SWOT analysis reveals that the availability of raw materials, involvement of local SMEs, and market trends are the main strengths and opportunities, despite challenges such as limited production facilities and competition in the market. Innovative products like corn ribs are proposed to add value to the commodity and support sustainable local economic growth. This study offers strategic recommendations for economic development based on local potential and provides guidelines for local governments in formulating policies for economic development in the related sectors.